A rare case of Rosai–Dorfman disease presenting as a pulmonary artery mass in a 33‐year‐old female with hypoxia - Veena Dronamraju; Kaitlyn McSurdy; Ryan Graham; Parth Rali; Maruti Kumaran; Daniela Proca; Bilal Lashari; Yoshiya Toyoda; Rohit Gupta (Pulmonary Circulation, 2023)
Abstract Rosai–Dorfman disease (RDD) is a rare form of non‐Langerhans histiocytosis. It is often idiopathic in etiology, but has been associated with viral, autoimmune, and malignant disease. Adequate diagnosis of RDD requires a combination of clinical symptoms, radiography, and histology. Most commonly, patients with RDD present with cervical lymphadenopathy. We describe a case of a young female who was initially thought to have a pulmonary embolism at the time of a COVID‐19 infection but was noted to have a rare occurrence of RDD presenting as a pulmonary artery mass upon further evaluation of radiology and histology. Though RDD is frequently benign, extranodal involvement can progress to end organ damage and must be recognized appropriately.